Rekonstruksi Kehujjahan Syar'u Man Qablana dalam Ushul Fikih Kontemporer: Analisis Perbedaan Pandangan Ulama dan Relevansinya terhadap Ijtihad Modern - Randi Hermawan; Dhiauddin Tanjung (Tabayyanu : Journal Of Islamic Law, 2024)
This study reconstructs the concept of the authoritativeness (ḥujjiyyah) of Shar'u Man Qablana within contemporary Usul al-Fiqh by re-examining classical scholarly debates and evaluating its relevance to modern ijtihad. Previous studies have predominantly focused on describing the divergent opinions of classical jurists regarding the legal status of pre-Islamic divine laws, while offering limited discussion on their epistemological reconstruction and practical significance for contemporary legal reasoning. Employing normative legal research, this study adopts conceptual, historical, comparative, and philosophical approaches. Primary sources consist of the Qur'an, Sunnah, and classical works of Usul al-Fiqh, complemented by recent scholarly literature on maqāṣid al-sharī'ah and contemporary Islamic legal theory. Data are analyzed through qualitative-prescriptive methods using grammatical, systematic, historical, comparative, and teleological (maqāṣid-based) interpretation. The findings demonstrate that the classical controversy over Shar'u Man Qablana reflects differing epistemological paradigms concerning the continuity of revelation and legal authority rather than a mere disagreement over the validity of earlier religious laws. This study argues that the classical legal-validity paradigm should be reconstructed into a legal-functionality paradigm by positioning Shar'u Man Qablana as an epistemological framework for identifying the continuity of universal legal objectives across prophetic revelations. As its principal contribution, this study proposes the Continuity of Maqāṣid-Based Reconstruction Model, which integrates the continuity of revelation, values, maqāṣid, and ijtihad into a coherent framework for contemporary Islamic legal reasoning. The model broadens the methodological role of Shar'u Man Qablana from a disputed subsidiary source of law to a dynamic interpretive framework capable of addressing emerging issues in Islamic law while preserving fidelity to the objectives of the Sharī'ah. This reconstruction enriches contemporary Usul al-Fiqh and provides a more adaptive methodology for modern ijtihad.